2013
DOI: 10.1177/1941406413476547
|View full text |Cite
|
Sign up to set email alerts
|

Photographic Examination of Student Lunches in Schools Using the Balanced School Day Versus Traditional School Day Schedules

Abstract: Therefore, the food a child eats depends on home nutritional practices and the perception of what parents think their child requires for energy at school."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 13 publications
0
16
1
Order By: Relevance
“…Photographic dietary assessment, previously validated in the literature [34,35,36,37,48,49], was modified for use in this study. The audio-video recording of meals, allowed for the independent collection of food data during deployments, with both a photographic and verbal recording of meals, prior to dining, replacing previous methods of self-report (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photographic dietary assessment, previously validated in the literature [34,35,36,37,48,49], was modified for use in this study. The audio-video recording of meals, allowed for the independent collection of food data during deployments, with both a photographic and verbal recording of meals, prior to dining, replacing previous methods of self-report (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…coffee in portable container). This method is a novel adaptation of the photographic food-logging method that has been used successfully in previous research [48,49] and has been deemed to be a more accurate and reliable method than self-report methods (i.e. recall) [34,35,36,37].…”
Section: Methodsmentioning
confidence: 99%
“…It is plausible that parents packing for 2 nutrition breaks may provide more food for their children in the BSD and may rely on more processed higher‐calorie convenience foods, resulting in unintended negative health consequences. Although this hypothesis is not supported by a study that assessed student lunches in 1 BSD and 1 TS school, it should be noted that the methods used to assess children's food consumption were not validated against a gold standard and the total sample size (N = 117) may have been inadequate to detect an effect …”
Section: Discussionmentioning
confidence: 94%
“…Principles of weight management in overweight/obese children include healthy snacks, portion control, limiting empty calorie drinks, and increasing physical activity. Dorman et al found students in a BSD school had significantly more beverages in packed lunches than students in a TS school; however, they found no differences in calorie content of lunches, which may be due to their reliance on children's self‐reports.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation